Model-Based Predictions of HIV Incidence Among African Women Using HIV Risk Behaviors and Community-Level Data on Male HIV Prevalence and Viral Suppression. (1st December 2020) - Moore, James R.; Donnell, Deborah J.; Boily, Marie-Claude; Mitchell, Kate M.; Delany-Moretlwe, Sinead; Bekker, Linda-Gail; Mgodi, Nyaradzo M.; El-Sadr, Wafaa; Cohen, Myron S.; Celum, Connie L.; Dimitrov, Dobromir
Abstract : Background: Pre-exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate and emtricitabine has proven highly effective in preventing HIV acquisition and is therefore offered to all participants in the control group as part of the standard of care package in many new HIV prevention studies. We propose a methodology for predicting HIV incidence in a hypothetical "placebo arm" for open-label studies or clinical trials with active control among African women. We apply the method to an open-label PrEP study, HIV Prevention Trials Network 082, which tested strategies to improve PrEP adherence in young African women all of whom were offered PrEP. Methods: Our model predicted HIV infection risk for female study cohorts in sub-Saharan Africa using baseline behavioral risk factors and contemporary HIV prevalence and viral suppression in the local male population. The model was calibrated to HIV incidence in the Vaginal and Oral Interventions to Control the Epidemic study. Results: Our model reproduced the annual HIV incidence of 3.2%–4.8% observed over 1 year of follow-up in the placebo groups of 4 completed clinical studies. We predicted an annual HIV incidence of 3.7% (95% confidence interval: 3.2 to 4.2) among HIV Prevention Trials Network 082 participants in the absence of PrEP and other risk reduction interventions. Conclusions: We demonstrated the potential of the proposed methodology to provide HIV incidence predictions based on assessment of individual risk behaviors and community and time-specific HIV exposure risk using HIV treatment and viral suppression data. These estimates may serve as comparators in HIV prevention trials without a placebo group. Abstract : Supplemental Digital Content is Available in the Text.